Petrogenesis of the Paleoproterozoic Näränkävaara layered intrusion, northern Finland, Part I : The northern peridotites and their relationships with the layered series and recharge events - Järvinen, Ville; Halkoaho, Tapio; Konnunaho, Jukka; Heinonen, Jussi S.; Karinen, Tuomo; Rämö, O. Tapani (Bulletin of the Geological Society of Finland, 2022)
The Paleoproterozoic Näränkävaara layered intrusion, northern Finland, has a surface area of 25 km x 5 km and a stratigraphic thickness of ~3 km. The main body of the intrusion includes a 1.5–2 km thick basal dunite series and a 1.3 km thick peridotitic-dioritic layered series, the latter with two peridotitic reversals related to magma recharge. In addition, a series of poorly known elongate poikilitic harzburgitic intrusions (the northern peridotites) are found along the NE contact between the intrusion and the granite-gneiss basement complex. We investigate new mineral and whole-rock geochemical data from the northern peridotites, with the aim of clarifying their petrogenetic relationship to the main layered body of the intrusion. The northern peridotites form a 200–400 m thick cumulate series grading from olivine orthocumulates (OC) at the northern basement complex contact to olivine-orthopyroxene heteradcumulates (HAC) towards the main intrusion body in the south. The OC show whole-rock and mineral chemical trends consistent with origin as rapidly cooled olivine-melt mixtures. The HAC have crystallized in situ from a relatively Cr- and SiO2-rich magma. Based on lithological and stratigraphical correlations, the northern peridotites are linked to the emplacement of the magma that caused the first reversal in the layered series: marginal orthocumulates were formed at the initial emplacement of a new pulse of LREE-enriched siliceous high-MgO basaltic (SHMB) magma into the Näränkävaara chamber, followed by heteradcumulate formation from a fractionating magma with added external SiO2 and fluid. Ubiquitous granite-gneiss xenoliths and felsic veins in drill core suggest assimilation may have been a local process. The northern peridotite parental magma shows undepleted metal ratios suggesting no sulfide saturation occurred prior to emplacement. Peer reviewed